2022
DOI: 10.1016/j.cub.2022.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine signaling in the dorsomedial striatum promotes compulsive behavior

Abstract: Compulsive behavior is a defining feature of disorders such as substance use disorders. Current evidence suggests that corticostriatal circuits control the expression of established compulsions, but little is known about the mechanisms regulating the development of compulsions. We hypothesized that dopamine, a critical modulator of striatal synaptic plasticity, could control alterations in corticostriatal circuits leading to the development of compulsions (defined here as continued reward seeking in the face o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Finally, it is possible that the balance between inhibition and disinhibition of DA neurons is altered by training, either by synaptic plasticity or by the recruitment of additional circuits during learning. We and others have observed that the in vivo patterns of DA axon activity and DA release in the DMS and the DLS change with training ( Hamid et al, 2021 ; Seiler et al, 2022 ; Willuhn et al, 2012 ). The reasons for training-induced changes in DA signaling are not yet clear, but with the approaches developed here and with additional innovations to adapt them for in vivo investigations, we can begin to rigorously address this hypothesis and advance our mechanistic understanding of the complex process of habit formation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Finally, it is possible that the balance between inhibition and disinhibition of DA neurons is altered by training, either by synaptic plasticity or by the recruitment of additional circuits during learning. We and others have observed that the in vivo patterns of DA axon activity and DA release in the DMS and the DLS change with training ( Hamid et al, 2021 ; Seiler et al, 2022 ; Willuhn et al, 2012 ). The reasons for training-induced changes in DA signaling are not yet clear, but with the approaches developed here and with additional innovations to adapt them for in vivo investigations, we can begin to rigorously address this hypothesis and advance our mechanistic understanding of the complex process of habit formation.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, it is possible that the balance between inhibition and disinhibition of DA neurons is altered by training, either by synaptic plasticity or by the recruitment of additional circuits during learning. We and others have observed that the in vivo patterns of DA axon activity and DA release in the DMS and the DLS change with training (Hamid et al, 2021;Seiler et al, 2022;Willuhn et al, 2012) Article ll OPEN ACCESS and advance our mechanistic understanding of the complex process of habit formation.…”
Section: Alternatives To the Ascending Spiral Hypothesismentioning
confidence: 88%
See 1 more Smart Citation
“…Conclusions were advanced on the grounds of anatomical studies and sparse functional evidence: one study tracked regionally shifting striatal dopamine signaling across development of a presumed habit reinforced by cocaine, 31 whereas another study reported no such shift using a natural reinforcer. 39 Thus, the central questions that remain are how region-specific and regionally shifting dopamine signals regulate habit formation.…”
Section: Introductionmentioning
confidence: 99%
“…Dopaminergic transmission in the striatum regulates reward processing (8). Specifically, dopamine in the nucleus accumbens core (NAcc) is critical for effortful responding for rewards, while dopamine in the dorsomedial striatum (DMS) is crucial for action-outcome learning and behavioral flexibility (9)(10)(11)(12). Dopaminergic transmission within the striatum occurs in two modes: tonic and phasic (13,14).…”
Section: Introductionmentioning
confidence: 99%